Роль культури мовлення у професійній діяльності - Геворк’ян, Л. А. (ХНУРЕ, 2020)
Professional communication is the speechinter action of a specialist with other specialists and clients of the organization in the course of professional activity. Professional culturelargely determine sits effectiveness, aswellas the reputation of the organizationas a who leand the individual specialist.
Keywords: культурне розмаїття; українознавство; традиції; культура